MELIHAT HIPERREALITAS GENERASI Z DAN PERAN PENTING AGAMA SEBAGAI KONTROL SOSIAL - Permadi, Danur Putut; Yantari, Hanif Fitri (Academic Journal of Islamic Principles and Philosophy, 2023)
This research aims to trace the forms of hyperreality that occur in generation Z and analyze the position of religion in addressing generation Z's problems. This research is motivated by the social changes of the generation Z. As a generation born and grows in the digital age, often generation Z chooses "life" in the social media world by prioritizing brands. The impact that will be caused by this hypperreality world is a consumptive generation. The data collection method in this study uses the documentation method. From the results of the study it was found that the form of hyperreality that occurred in generation Z included in the world of fashion they prioritized the name of the brand. The name of the brand plays an important role in constructing people's views on them. Besides that, other forms of hyperreality among generation Z are that they use social media as primary needs. Social media actually becomes a place where the young world is. In such conditions religion has a central role as a guide for generation Z to not be compatible and excessive in living life.